2015
DOI: 10.20289/euzfd.34605
|View full text |Cite
|
Sign up to set email alerts
|

Farm Operations Cooperative in Central Agricultural Zone of Delta State, Nigeria

Abstract: ABSTRACThis study was carried out to examine farm operations cooperatives in Central Agricultural Zone of Delta State, Nigeria. All the members of the six (6) selected groups were used for the study. The data which were collected with the use of questionnaire and interview schedule were analyzed with the use of frequency counts, percentages and tobit regression model. Most of the members were females and were also mostly married. Most of them were educated formally and had average household size of 5 persons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
1
1
1
Order By: Relevance
“…The mean farm size of leaders and members were 3.8±2.4 hectares and 3.2±2.03 hectares respectively, implying that the majority of the leaders and members had small farm sizes. This agrees with the findings of Yamusa and Adefila (2014) and Ofuoku (2015), that the majority of farmers were operating on a small scale and unable to benefit from economies of scale hence resorting to cooperative organizations. Further results show that the mean annual income of the leaders and members were N1,581,000:00 ± N935,223.85 and N1,286,666.67 ± N 855,662.14 respectively which (at 1USD = N 600), are equivalent to US$2635 ± US$1558.71 for leaders and US$2,144.44 ± US$1426.10 for members.…”
Section: Demographic Attributessupporting
confidence: 92%
See 1 more Smart Citation
“…The mean farm size of leaders and members were 3.8±2.4 hectares and 3.2±2.03 hectares respectively, implying that the majority of the leaders and members had small farm sizes. This agrees with the findings of Yamusa and Adefila (2014) and Ofuoku (2015), that the majority of farmers were operating on a small scale and unable to benefit from economies of scale hence resorting to cooperative organizations. Further results show that the mean annual income of the leaders and members were N1,581,000:00 ± N935,223.85 and N1,286,666.67 ± N 855,662.14 respectively which (at 1USD = N 600), are equivalent to US$2635 ± US$1558.71 for leaders and US$2,144.44 ± US$1426.10 for members.…”
Section: Demographic Attributessupporting
confidence: 92%
“…This implies that although both leaders and their members had enough farming experience, leaders of cooperative societies had more farming experience than their members which could influence their performance. The finding is at variance from that of Yamusa and Adefila (2014) and Ofuoku (2015) who reported that members of farmers' cooperative societies had longer years of farming experience. The mean farm size of leaders and members were 3.8±2.4 hectares and 3.2±2.03 hectares respectively, implying that the majority of the leaders and members had small farm sizes.…”
Section: Demographic Attributescontrasting
confidence: 88%
“…For instance, due to climate change, herders (who are primarily men and usually assisted by boys in Nigeria) and their cattle are often forced to navigate undefined routes to the relatively greener vegetated southern belt in search of feed [36][37][38]. In the process, some herders invade farms with their cattle that forage on crops and destroy seeds, thereby resulting in frequent land-use conflicts with cassava farmers and a loss of their livelihoods [39][40][41][42][43][44][45][46]. In extreme cases, conflict leads to some farmers migrating off their lands [33].…”
Section: Introductionmentioning
confidence: 99%